2000
DOI: 10.1046/j.1440-1754.2000.00496.x
|View full text |Cite
|
Sign up to set email alerts
|

Paroxysmal non‐epileptic events in children: A retrospective study over a period of 10 years

Abstract: Paroxysmal non-epileptic events can cause diagnostic confusion, particularly in children with developmental delay, epilepsy or an epileptiform EEG. Accurate diagnosis can be reached in the majority of cases using video EEG monitoring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
98
0
4

Year Published

2000
2000
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(109 citation statements)
references
References 21 publications
7
98
0
4
Order By: Relevance
“…In support of this view, a retrospective study of paroxysmal nonepileptic events in 666 pediatric patients found 7% of all events to be shuddering attacks. 11 Further investigations in affected infants are usually not indicated. Reassurance of parents is crucial since relatives are often frightened by the unexpected appearance and often high frequency of the attacks.…”
Section: Go To Sectionmentioning
confidence: 99%
“…In support of this view, a retrospective study of paroxysmal nonepileptic events in 666 pediatric patients found 7% of all events to be shuddering attacks. 11 Further investigations in affected infants are usually not indicated. Reassurance of parents is crucial since relatives are often frightened by the unexpected appearance and often high frequency of the attacks.…”
Section: Go To Sectionmentioning
confidence: 99%
“…[7][8][9][10][11][12][13][14] Although the presentation of specific disorders has been described in detail, the literature contains only scant data concerning the relative frequency of various types of PNEs in children and adolescents. Recently, Bye et al 15 reported that PNEs accounted for 43% of children who underwent video-electroencephalographic (EEG) monitoring. In our study, we have examined the relative frequency of different PNE disorders encountered during a 6-year period in our Pediatric Epilepsy Monitoring Unit (PEMU).…”
mentioning
confidence: 99%
“…Video-EEG epileptik nöbetlerin klinik ve EEG özelliklerinin belirlenmesinin yanı sıra nonepileptik paroksismal olayların tanımlan-masında da kullanılır; nonepileptik olayların tanısında altın standart kabul edilmektedir. [15] Çocukluk çağında iktal semiyolojiyi değerlendirirken nö-betlerin yaş ve nörolojik gelişimle birlikte değişeceği, eriş-kin yaş grubundan farklı klinik davranış özellikleri ve EEG bulguları göstereceğinin bilinmesi gerekir. [16][17][18][19][20][21][22] Örneğin 7 yaş altı çocuklarda frontal lob epilepsi daha çok epileptik spazm, belirsiz davranış değişiklikleri, spontan aktivitenin durması gibi bulgular verir; temporal lob epilepsi hem motor hem EEG bulguları açısıdan fokal bulgular yerine diffüz/ bilateral özellikler gösterebilir.…”
Section: çOcukluk çAğında Epilepsi Cerrahisi öNcesi Değerlendir-meunclassified